2019
DOI: 10.21071/az.v68i261.3949
|View full text |Cite
|
Sign up to set email alerts
|

Diversidade genética em caprino Marota e manejo genético para rebanhos de conservação

Abstract: ¹Universidade Federal do Piauí. Brasil. ²Universidade Estadual de São Paulo. Brasil. ³Embrapa Meio Norte. Brasil. Palavras chave adicionais Microarranjos. Recursos genéticos. Risco de extinção. SNP.resUMo Objetivou-se avaliar a diversidade genética em rebanhos de caprinos Marota e verificar o impacto do uso de marcadores moleculares no manejo genético em rebanho de conservação. Utilizando-se Chip SNP caprino 50K genotipou-se 76 animais do rebanho de conservação institucional e 10 animais de um rebanho particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The results showed that all paired FST values between populations were statistically significant (p<0.01). In our study, high genetic differentiation (FST=0.16) was observed between the Marota gene group and the Anglo-Nubian breed, indicating that Marota has considerable genetic diversity, suggesting that natural selection may have been a key factor in shaping the genetic diversity detected in this breed ( Oliveira Moura et al, 2019 a).…”
Section: Resultsmentioning
confidence: 45%
See 3 more Smart Citations
“…The results showed that all paired FST values between populations were statistically significant (p<0.01). In our study, high genetic differentiation (FST=0.16) was observed between the Marota gene group and the Anglo-Nubian breed, indicating that Marota has considerable genetic diversity, suggesting that natural selection may have been a key factor in shaping the genetic diversity detected in this breed ( Oliveira Moura et al, 2019 a).…”
Section: Resultsmentioning
confidence: 45%
“…At first, genetic structuring analyses based on the main components revealed that the cluster number that explains the genomic variation data more clearly, between the Marota genetic group and the Anglo-Nubian breed, was K = 2 for analysis of SNPs markers. In this sense, when the subpopulations are represented in the Cartesian plane, constituted by the first two main components, there was a clear separation between the groups of animals ( Figure2 ), with an individual from the distinct groups closely related genetically, which indicates that there is a mixed between breeds ( Oliveira Moura et al, 2019 a)…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Among livestock species, goats (Capra hircus) play a crucial role in economic development, significantly contributing to large-scale production, particularly of milk, and supporting rural subsistence by enhancing income for families in developing countries [1,2]. In the Brazilian context, farming activities involving small ruminants are divided between large producers and small breeders, with goats prominently adapted to the semi-arid tropics [3,4]. Goat landraces are generally more genetically diverse than commercial breeds, as they have been developed through a long history of breeding by processes markedly different from those used for commercial breeds.…”
Section: Introductionmentioning
confidence: 99%